How can economists use the cognitive challenges framework to enhance economic education?. Issue 1 (23rd December 2020) - Allgood, Sam; McGoldrick, KimMarie
Abstract: Chew and Cerbin (2021 ) outline nine cognitive challenges to student learning with which economic educators are likely familiar, even if the language used to describe them differs. In this article, the authors refrain from summarizing Chew and Cerbin's framework and instead focus on providing context for how those conducting research and developing pedagogy in economics might incorporate these challenges into their work. In addition, they provide some thoughts on what these challenges mean for two important related issues: improving diversity and inclusion in the economics profession and the training of teachers in economics.